Hard carbon material and preparation method and application thereof
Through multi-stage extraction and high-temperature carbonization technology of cheap aromatic rich hydrocarbon oil, hard carbon materials with high layer spacing and conductivity were prepared, which solved the problems of high preparation cost of asphalt-based hard carbon materials and insufficient electrochemical performance, and realized sodium ion batteries performance improvement and cost reduction.
Patent Information
- Application Number
- CN202411436635.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-15
AI Technical Summary
The existing asphalt-based hard carbon materials have high preparation costs and need to be further improved in electrochemical performance, making it difficult to meet the performance requirements of sodium ion batteries.
Using cheap aromatic oil as raw material, specific extraction components are obtained through multi-stage extraction, and hard carbon materials are prepared through pre-carbonization and high-temperature carbonization. They are used as the positive electrode material of sodium ion batteries to improve their layer spacing, conductivity and storage capacity. .
It significantly reduces the production cost of sodium ion batteries, improves specific capacity, rate performance and cycle stability, provides a low-cost and excellent performance hard carbon positive electrode material, and promotes the development of sodium ion batteries.
Smart Images

Figure BDA0005085193420000161
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hard carbon materials, and in particular to a hard carbon material and a preparation method and application thereof. Background Art
[0002] With the transformation of the global energy structure and the increasing emphasis on environmental protection, the research and development of new energy battery technology has become the focus of global attention. As the core components of new energy vehicles, portable electronic devices, large-scale energy storage and other fields, new energy batteries have developed rapidly in recent years. With the rapid development of lithium-ion batteries and the shortage of lithium resources, sodium-ion batteries, which have similar electrochemical properties and rich content to lithium-ion batteries, have gradually shown good commercial potential.
[0003] Hard carbon is a kind of carbon that is difficult to graphitize. Due to the presence of a large number of heteroatoms such as H, O, and N in its precursor, the formation of crystalline regions during heat treatment is hindered, so it is difficult to graphitize even at high temperatures above 2800°C. Its internal structure is highly irregular and disordered, mainly composed of disordered stacking of small-sized graphene sheets, which is generally described as a "falling card" model. Compared with graphite materials, hard carbon has more sodium ion storage sites and can better meet people's high energy storage requirements. In addition, hard carbon also has an isotropic structural feature, and its interlayer spacing is larger than the graphite interlayer spacing (interlayer spacing d002>0.36nm), which facilitates the transportation and diffusion of sodium ions. At the same time, its cycle performance and rate performance are good and the cost is low.
[0004] Asphalt has a high coking value, a wide range of sources, and a low price, and has obvious advantages as a hard carbon precursor. At present, the preparation method of conventional asphalt-based hard carbon materials is to oxidize the asphalt for pretreatment, obtain a precursor material after curing and cross-linking, and then carbonize and crush the precursor material under an inert atmosphere to obtain an asphalt-based hard carbon material. However, untreated asphalt is prone to form a graphite-like structure during the carbonization process. Therefore, when it is used to prepare hard carbon, the asphalt needs to be pretreated or pre-oxidized, which increases the preparation cost of asphalt-based hard carbon. As the price of lithium carbonate continues to decline, in order to increase the advantages of sodium-ion batteries, the development of lower-cost hard carbon is imperative. Summary of the invention
[0005] In view of the high preparation cost of existing asphalt-based hard carbon materials and the need to further improve electrochemical performance, the present invention provides a hard carbon material and its preparation method and application. The present invention uses cheap aromatic-rich oil as raw material, undergoes multi-stage extraction, and pre-carbonizes and high-temperature carbonizes specific extraction components to hard carbon materials. The sodium ion battery prepared using the hard carbon material as the positive electrode material has the advantages of high compaction density, high initial efficiency and high capacity retention rate, and effectively reduces the production cost of sodium ion batteries, and has broad application prospects in the field of sodium ion batteries.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] In a first aspect, the present invention provides a method for preparing a hard carbon material, comprising the following steps:
[0008] S1, mixing the aromatics-rich oil and the primary extraction solvent uniformly, heating for extraction, and performing solid-liquid separation to obtain a primary extraction liquid; removing the solvent from the primary extraction liquid to obtain a primary extract;
[0009] S2, mixing the primary extract and the secondary extraction solvent uniformly, heating for extraction, and performing solid-liquid separation to obtain a secondary extract residue;
[0010] S3, uniformly mixing the secondary raffinate and the tertiary extraction solvent, heating for extraction, cooling, solid-liquid separation, and drying to obtain a tertiary raffinate;
[0011] S4, pre-carbonizing the tertiary extract at 350°C to 550°C, and then high-temperature carbonizing at 750°C to 1600°C under an inert atmosphere, and crushing to obtain a hard carbon material.
[0012] Wherein, the polarity of the primary extraction solvent is greater than that of the tertiary extraction solvent and greater than that of the secondary extraction solvent, and the secondary extraction solvent is a non-polar solvent.
[0013] Compared with the prior art, the preparation method of the hard carbon material provided by the present invention uses cheap ethylene tar as raw material, adopts a solvent of specific polarity to perform three-stage extraction on ethylene tar, and obtains aromatic substances and colloidal components in ethylene tar. Most of these substances are strong polar components, and the structure contains more oxygen-containing functional groups. The hard carbon material prepared by pre-carbonization and high-temperature carbonization using this component as a precursor has a large interlayer spacing, which is conducive to the embedding and extraction of sodium ions, reduces the diffusion path of sodium ions in the hard carbon material, and provides more storage space for sodium ions. At the same time, it also helps to alleviate the volume expansion and contraction of the material during charging and discharging. In addition, the colloidal component can form a cross-linked structure in the hard carbon material, improve the conductivity and structural stability of the hard carbon material, and the cross-linked structure can form more micropores and defects. These micropores and defects can be used as sodium storage points to increase the storage capacity of sodium ions, and the cross-linked structure can also increase the surface roughness of the hard carbon material, improve the wettability of the electrolyte, thereby improving the charging and discharging performance of the sodium ion battery.
[0014] Using the hard carbon material prepared by the present invention as the positive electrode material of the sodium ion battery can significantly improve the specific capacity, rate performance and cycle stability of the sodium ion battery, providing a low-cost, high-performance hard carbon positive electrode material for the sodium ion battery, achieving the purpose of reducing costs and increasing efficiency, which is of great significance for promoting the development of sodium ion batteries and has a high value for promotion and application.
[0015] Furthermore, in S1, the aromatics-rich oil includes at least one of ethylene tar, catalytic cracking slurry, medium- and low-temperature coal tar or bio-tar.
[0016] Preferably, in S1, the aromatics-rich oil is ethylene tar.
[0017] It should be noted that the softening point (SP) of the ethylene tar in the present invention is < 25°C.
[0018] Most asphalts are obtained from the thermal polymerization and thermal polycondensation of ethylene tar raw materials. The present invention directly uses cheap ethylene tar as raw material, undergoes multi-stage extraction, and uses the extracted material as a precursor to prepare hard carbon materials, which not only significantly improves the electrochemical properties of hard carbon materials, but also significantly reduces the preparation cost of hard carbon materials, providing a low-cost and excellent performance positive electrode material for sodium ion batteries.
[0019] Furthermore, in S1, the primary extraction solvent includes at least one of quinoline, chloroform, 3-pentanone, 1,1-dichloroethane or cyclohexanone.
[0020] Preferably, in S1, the primary extraction solvent is quinoline.
[0021] Furthermore, in S1, the temperature of the heating extraction is 70°C to 90°C, and the time of the heating extraction is 50min to 70min.
[0022] Furthermore, in S1, the mass volume ratio of the aromatic-rich oil to the primary extraction solvent is 1 g:4 mL to 1 g:6 mL.
[0023] Preferably, in S1, the mass volume ratio of the aromatic-rich oil to the primary extraction solvent is 1 g:5 mL.
[0024] Furthermore, in S2, the secondary extraction solvent is at least one of mid-boiling range petroleum ether, n-pentane, n-octane, cyclohexane or cyclopentane.
[0025] Preferably, in S2, the secondary extraction solvent is medium-boiling range petroleum ether.
[0026] Furthermore, the mass volume ratio of the primary extract and the secondary extraction solvent is 1g:2mL to 1g:4mL.
[0027] Preferably, the mass volume ratio of the primary extract to the secondary extraction solvent is 1 g:3 mL.
[0028] Furthermore, in S2, the temperature of the heating extraction is 40°C to 60°C, and the time of the heating extraction is 20min to 40min.
[0029] Furthermore, in S3, the tertiary extraction solvent is at least one of n-butanol, isobutanol, amyl alcohol or isopropanol.
[0030] Preferably, in S3, the tertiary extraction solvent is n-butanol.
[0031] Furthermore, in S3, the mass volume ratio of the secondary raffinate to the tertiary extraction solvent is 1 g:3 mL to 1 g:5 mL.
[0032] Preferably, in S3, the mass volume ratio of the secondary raffinate to the tertiary extraction solvent is 1 g:4 mL.
[0033] Furthermore, in S3, the temperature of the heating extraction is 50°C to 70°C, and the time of the heating extraction is 50min to 70min.
[0034] It should be noted that in S3, after cooling to a temperature lower than the boiling point of the tertiary extraction solvent, suction filtration is performed while hot to obtain a tertiary extraction residue.
[0035] It should be noted that in the above S1 to S3, the extraction process is carried out in a stainless steel reactor at normal pressure, and stirring is performed during the extraction process.
[0036] Taking quinoline, medium boiling range petroleum ether and n-butanol as examples, the principle of the extraction process in the present invention is as follows:
[0037] Ethylene tar is extracted with quinoline, and the quinoline insolubles obtained by extraction exclude the components of quinoline insolubles, leaving only saturated parts, aromatic parts and gum components. After extraction with petroleum ether, the petroleum ether insolubles obtained exclude most of the saturated parts, leaving only substances mainly composed of aromatic parts and gum components. n-Butanol has a strong alkane solubility, so it has a large solubility for saturated components mainly composed of alkanes. At the same time, it has a good solubility for hydroxyl polar components with slightly stronger polarity. Therefore, the n-butanol insolubles basically exclude most of the aromatic parts with slightly worse polarity and a small part of gum with lower polarity. The obtained n-butanol insolubles contain a small part of aromatic parts with strong polarity and most of the gum components with strong polarity. The hard carbon material obtained using this component as a precursor has a cross-linked structure with a large interlayer spacing, which is suitable as a hard carbon material for the positive electrode of a sodium ion battery.
[0038] Further, in S4, the temperature is raised to 350°C to 550°C at a rate of 3°C / min to 8°C / min, and the pre-carbonization time is 0.5h to 2h.
[0039] It should be noted that the pre-carbonization was performed in an air atmosphere.
[0040] Further, in S4, the temperature is raised to 750°C to 1600°C at a rate of 3°C / min to 8°C / min, and the high temperature carbonization time is 2h to 10h.
[0041] Pre-carbonizing and high-temperature carbonizing the precursor obtained by the tertiary extraction can eliminate the unstable components in the precursor as much as possible, and is beneficial to improving the microstructure and electrochemical properties of the hard carbon material, thereby improving the overall performance of the sodium ion battery.
[0042] It should be noted that in S4, D50 of the hard carbon material is 5 μm to 7 μm.
[0043] Further, in S4, the inert atmosphere is provided by an inert gas. The inert gas may be conventional nitrogen, argon, helium, etc. in the art. Specifically, the inert gas has an inlet flow rate of 1 L / min to 2 L / min.
[0044] In a second aspect, the present invention further provides a hard carbon material prepared by any of the above-mentioned methods for preparing the hard carbon material.
[0045] In a third aspect, the present invention further provides a positive electrode, comprising the hard carbon material.
[0046] In a fourth aspect, the present invention also provides the use of the above-mentioned hard carbon material or the above-mentioned positive electrode in the preparation of a sodium ion battery.
[0047] In a fifth aspect, the present invention also provides a sodium ion battery, comprising the above-mentioned hard carbon material or the above-mentioned positive electrode.
[0048] In a sixth aspect, the present invention further provides a battery module, comprising the above-mentioned sodium ion battery.
[0049] The present invention uses ethylene tar as a raw material, performs multi-stage extraction with an extraction solvent of a specific polarity to obtain a precursor material, and then obtains a hard carbon material through pre-carbonization and high-temperature carbonization. Using it as a sodium ion positive electrode material is beneficial to the deintercalation and rapid charge and discharge performance of sodium ions, and is also beneficial to improving the cycle stability performance of sodium ion batteries and improving the overall performance of sodium ion batteries. In addition, the cost of ethylene tar is relatively low. Using it as a raw material to prepare a hard carbon material not only improves the overall performance of sodium ion batteries, but also helps to reduce the production cost of sodium ion batteries. It has obvious economic and market advantages, and provides a hard carbon material with excellent comprehensive performance for sodium ion batteries, with broad market prospects. DETAILED DESCRIPTION
[0050] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0051] In order to better illustrate the present invention, further examples are given below.
[0052] Example 1
[0053] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0054] Step a, weighing 300g of ethylene tar (SP<25℃) and 1500mL of quinoline into a stainless steel reactor at normal pressure, heating to 80℃, stirring and extracting for 60min, filtering while hot to obtain quinoline solubles; distilling the quinoline solubles to remove the solvent to obtain a quinoline soluble extract;
[0055] Step b, weighing 100 g of the quinoline soluble extract and 300 mL of medium boiling range (60-90° C.) petroleum ether into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 min, and filtering while hot to obtain petroleum ether insoluble matter;
[0056] Step c, weighing 30 g of the petroleum ether insoluble matter and 120 mL of n-butanol, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain n-butanol insoluble matter;
[0057] Step d, transfer 10g of the above-mentioned n-butanol insoluble matter to an open tubular furnace, heat it to 360℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 1350℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 2h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0058] Example 2
[0059] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0060] Step a, weighing 300g of ethylene tar (SP<25℃) and 1500mL of cyclohexanone into a stainless steel reactor at normal pressure, heating to 70℃, stirring and extracting for 70min, filtering while hot to obtain cyclohexanone solubles; distilling the cyclohexanone solubles to remove the solvent to obtain a cyclohexanone soluble extract;
[0061] Step b, weighing 100 g of the cyclohexanone soluble extract and 300 mL of medium boiling range (60-90° C.) petroleum ether into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 min, and filtering while hot to obtain petroleum ether insoluble matter;
[0062] Step c, weighing 30 g of the petroleum ether insoluble matter and 110 mL of n-butanol, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain n-butanol insoluble matter;
[0063] Step d, transfer 10g of the above-mentioned n-butanol insoluble matter to an open tubular furnace, heat it to 400℃ at a rate of 5℃ / min, and keep it at a constant temperature for 1.5h for pre-carbonization, then switch to a closed tubular furnace, introduce argon gas with a flow rate of 1.5L / min, heat it to 1450℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 3h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0064] Example 3
[0065] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0066] Step a, weighing 300g of ethylene tar (SP<25℃) and 1800mL of chloroform into a stainless steel reactor at normal pressure, heating to 80℃, stirring and extracting for 60min, filtering while hot to obtain chloroform soluble matter; distilling the chloroform soluble matter to remove the solvent to obtain a chloroform soluble extract;
[0067] Step b, weighing 100 g of the chloroform-soluble extract and 200 mL of medium-boiling range (60-90° C.) petroleum ether, adding them into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 minutes, and filtering while hot to obtain petroleum ether insoluble matter;
[0068] Step c, weighing 30 g of the petroleum ether insoluble matter and 90 mL of n-butanol, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain n-butanol insoluble matter;
[0069] Step d, transfer 10g of the above-mentioned n-butanol insoluble matter to an open tubular furnace, heat it to 500℃ at a rate of 5℃ / min, and keep it at a constant temperature for 1h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 1550℃ at a rate of 6℃ / min, keep it at this temperature for carbonization for 6h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0070] Example 4
[0071] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0072] Step a, weighing 300g of ethylene tar (SP<25℃) and 1600mL of 3-pentanone into a stainless steel reactor at normal pressure, heating to 90℃, stirring and extracting for 50min, filtering while hot to obtain 3-pentanone soluble matter; distilling the 3-pentanone soluble matter to remove the solvent to obtain a 3-pentanone soluble extract;
[0073] Step b, weighing 100 g of the above 3-pentanone soluble extract and 400 mL of medium boiling range (60-90° C.) petroleum ether, adding them into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 minutes, and filtering while hot to obtain petroleum ether insoluble matter;
[0074] Step c, weighing 30 g of the petroleum ether insoluble matter and 150 mL of isopropanol, adding them into a closed stainless steel reactor at normal pressure, heating to 65° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain the isopropanol insoluble matter;
[0075] Step d, transfer 10g of the above-mentioned isopropanol insoluble material to an open tubular furnace, heat it to 360℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 1200℃ at a rate of 7℃ / min, keep it at this temperature for carbonization for 7h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=7μm.
[0076] Example 5
[0077] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0078] Step a, weighing 300g of ethylene tar (SP<25℃) and 1200mL of 1,1-dichloroethane into a stainless steel reactor at normal pressure, heating to 85℃, stirring and extracting for 60min, filtering while hot to obtain 1,1-dichloroethane solubles; distilling the 1,1-dichloroethane solubles to remove the solvent to obtain 1,1-dichloroethane soluble extracts;
[0079] Step b, weighing 100 g of the above 1,1-dichloroethane soluble extract and 350 mL of medium boiling range (60-90° C.) petroleum ether, adding them into a closed stainless steel reactor at normal pressure, heating to 45° C., stirring and extracting for 35 minutes, and filtering while hot to obtain petroleum ether insoluble matter;
[0080] Step c, weighing 30 g of the petroleum ether insoluble matter and 130 mL of n-butanol, adding them into a closed stainless steel reactor at normal pressure, heating to 70° C., stirring and extracting for 50 min, cooling to below 60° C., filtering while hot, and drying to obtain n-butanol insoluble matter;
[0081] Step d, transfer 10g of the above-mentioned n-butanol insoluble matter to an open tubular furnace, heat it to 370℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 1400℃ at a rate of 8℃ / min, keep it at this temperature for carbonization for 3h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=5μm.
[0082] Example 6
[0083] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0084] Step a, weighing 300g of ethylene tar (SP<25℃) and 1300mL of quinoline into a stainless steel reactor at normal pressure, heating to 75℃, stirring and extracting for 65min, filtering while hot to obtain quinoline solubles; distilling the quinoline solubles to remove the solvent to obtain a quinoline soluble extract;
[0085] Step b, weighing 100 g of the quinoline soluble extract and 250 mL of n-pentane, adding them into a closed stainless steel reactor at normal pressure, heating to 55° C., stirring and extracting for 30 min, and filtering while hot to obtain n-pentane insoluble matter;
[0086] Step c, weighing 30 g of the above n-pentane insoluble matter and 120 mL of amyl alcohol, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain amyl alcohol insoluble matter;
[0087] Step d, transfer 10g of the above-mentioned pentanol insoluble matter to an open tubular furnace, heat it to 380℃ at a rate of 7℃ / min, and keep it at a constant temperature for 1.5h for pre-carbonization, then switch to a closed tubular furnace, introduce argon gas with a flow rate of 1.5L / min, heat it to 1100℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 4h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0088] Example 7
[0089] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0090] Step a, weighing 300g of ethylene tar (SP<25℃) and 1400mL of quinoline into a stainless steel reactor at normal pressure, heating to 85℃, stirring and extracting for 55min, filtering while hot to obtain quinoline solubles; distilling the quinoline solubles to remove the solvent to obtain a quinoline soluble extract;
[0091] Step b, weighing 100 g of the quinoline soluble extract and 360 mL of n-octane, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 20 min, and filtering while hot to obtain n-octane insoluble matter;
[0092] Step c, weighing 30 g of the above n-octane insoluble matter and 140 mL of n-butanol, adding them into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 70 min, cooling to below 60° C., filtering while hot, and drying to obtain n-butanol insoluble matter;
[0093] Step d, transfer 10g of the above-mentioned n-butanol insoluble matter to an open tubular furnace, heat it to 400℃ at a rate of 5℃ / min, and keep it at a constant temperature for 1.5h for pre-carbonization, then switch to a closed tubular furnace, introduce argon gas with a flow rate of 1.5L / min, heat it to 850℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 5h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0094] Example 8
[0095] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0096] Step a, weighing 300g of ethylene tar (SP<25℃) and 1500mL of quinoline into a stainless steel reactor at normal pressure, heating to 80℃, stirring and extracting for 60min, filtering while hot to obtain quinoline solubles; distilling the quinoline solubles to remove the solvent to obtain a quinoline soluble extract;
[0097] Step b, weighing 100 g of the quinoline soluble extract and 320 mL of cyclohexane, adding them into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 min, and filtering while hot to obtain cyclohexane insoluble matter;
[0098] Step c, weighing 30 g of the above cyclohexane insoluble matter and 150 mL of isobutanol, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain the isobutanol insoluble matter;
[0099] Step d, transfer 10g of the above-mentioned isobutanol insoluble matter to an open tubular furnace, heat it to 350℃ at a rate of 6℃ / min, keep it at a constant temperature for 1h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 750℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 10h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0100] Example 9
[0101] This embodiment provides a method for preparing a hard carbon material, comprising the following steps:
[0102] Step a, weighing 300g of ethylene tar (SP<25℃) and 1450mL of quinoline into a stainless steel reactor at normal pressure, heating to 80℃, stirring and extracting for 60min, filtering while hot to obtain quinoline solubles; distilling the quinoline solubles to remove the solvent to obtain a quinoline soluble extract;
[0103] Step b, weighing 100 g of the quinoline soluble extract and 340 mL of cyclopentane, adding them into a closed stainless steel reactor at normal pressure, heating to 40° C., stirring and extracting for 40 min, and filtering while hot to obtain cyclopentane insoluble matter;
[0104] Step c, weighing 30 g of the above cyclopentane insoluble matter and 120 mL of n-butanol, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain n-butanol insoluble matter;
[0105] Step d, transfer 10g of the above-mentioned n-butanol insoluble matter to an open tubular furnace, heat it to 550℃ at a rate of 8℃ / min, keep it at a constant temperature for 0.5h for pre-carbonization, then switch to a closed tubular furnace, introduce argon gas with a flow rate of 1.5L / min, heat it to 1600℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 2h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0106] Comparative Example 1
[0107] This comparative example provides a method for preparing a hard carbon material, comprising the following steps:
[0108] Step a, weigh 300g of ethylene tar (SP<25℃) and place it in a high-temperature reactor, heat it from room temperature to 200℃ and keep it warm for 1h, then heat it to 340℃ at a rate of 1℃ / min under argon atmosphere, and keep the pressure at 0.2MPa for 6h to obtain liquid asphalt;
[0109] Step b, transferring the above liquid asphalt into a round-bottom flask, replacing the atmosphere of the round-bottom flask with air having an oxygen content of 60%, with a gas flow rate of 40 mL / min, and keeping the temperature at 320° C. for 2 h, cooling, filtering, and crushing to obtain a precursor;
[0110] Step c, transfer 10g of the above precursor to an open tubular furnace, heat it to 360℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h for pre-carbonization, then switch to a closed tubular furnace, introduce argon with a flow rate of 1.5L / min, heat it to 1350℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 2h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0111] Comparative Example 2
[0112] This comparative example provides a method for preparing a hard carbon material. The only difference from Example 1 is that n-butanol soluble matter is selected in step c. The specific steps are as follows:
[0113] Step a, weighing 300g of ethylene tar (SP<25℃) and 1500mL of quinoline into a stainless steel reactor at normal pressure, heating to 80℃, stirring and extracting for 60min, filtering while hot to obtain quinoline solubles; distilling the quinoline solubles to remove the solvent to obtain a quinoline soluble extract;
[0114] Step b, weighing 100 g of the quinoline soluble extract and 300 mL of medium boiling range (60-90° C.) petroleum ether into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 min, and filtering while hot to obtain petroleum ether insoluble matter;
[0115] Step c, weighing 30 g of the petroleum ether insoluble matter and 120 mL of n-butanol into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C. and filtering while hot to obtain n-butanol soluble matter; distilling the n-butanol soluble matter to remove the solvent to obtain a n-butanol soluble extract;
[0116] Step d, transfer 10g of the above-mentioned n-butanol soluble extract to an open tubular furnace, heat it to 360℃ at a rate of 5℃ / min, and keep it at a constant temperature for 2h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 1350℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 2h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0117] Comparative Example 3
[0118] This comparative example provides a method for preparing a hard carbon material. The only difference from Example 1 is that petroleum ether solubles are selected in step b. The specific steps are as follows:
[0119] Step a, weighing 300g of ethylene tar (SP<25℃) and 1500mL of quinoline into a stainless steel reactor at normal pressure, heating to 80℃, stirring and extracting for 60min, filtering while hot to obtain quinoline solubles; distilling the quinoline solubles to remove the solvent to obtain a quinoline soluble extract;
[0120] Step b, weighing 100 g of the quinoline soluble extract and 300 mL of medium boiling range (60-90° C.) petroleum ether, adding them into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 minutes, filtering while hot to obtain a petroleum ether soluble matter; removing the solvent from the petroleum ether soluble matter to obtain a petroleum ether soluble extract;
[0121] Step c, weighing 30 g of the petroleum ether soluble extract and 120 mL of n-butanol, adding them into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain n-butanol insoluble matter;
[0122] Step d, transfer 10g of the above-mentioned n-butanol insoluble matter to an open tubular furnace, heat it to 360℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 1350℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 2h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0123] Comparative Example 3
[0124] This comparative example provides a method for preparing a hard carbon material, which is different from Example 1 only in that quinoline in step a of Example 1 replaces an equal amount of toluene, and a toluene-soluble extract is obtained. The rest is exactly the same and will not be repeated here.
[0125] Comparative Example 4
[0126] This comparative example provides a method for preparing a hard carbon material, which is different from Example 1 only in that the medium-boiling petroleum ether in step b of Example 1 is replaced with an equal amount of N-methylpyrrolidone to obtain N-methylpyrrolidone insoluble matter, and the rest is exactly the same and will not be repeated here.
[0127] Comparative Example 5
[0128] This comparative example provides a method for preparing a hard carbon material, which is different from Example 1 only in that the medium-boiling petroleum ether in step b of Example 1 is replaced with an equal amount of tetrahydrofuran to obtain tetrahydrofuran insoluble matter, and the rest is exactly the same and will not be repeated here.
[0129] Comparative Example 6
[0130] This comparative example provides a method for preparing a hard carbon material, which is different from Example 1 only in that n-butanol in step c of Example 1 is substituted for an equal amount of ethanol to obtain ethanol insoluble matter, and the rest is exactly the same and will not be repeated here.
[0131] Comparative Example 7
[0132] This comparative example provides a method for preparing a hard carbon material, the only difference being that the extraction solvents in step a and step c are exchanged. The specific steps are as follows:
[0133] Step a, weighing 300g of ethylene tar (SP<25℃) and 1500mL of n-butanol into a stainless steel reactor at normal pressure, heating to 80℃, stirring and extracting for 60min, filtering while hot to obtain n-butanol soluble matter; distilling the n-butanol soluble matter to remove the solvent, to obtain a n-butanol soluble extract;
[0134] Step b, weighing 100 g of the above n-butanol soluble extract and 300 mL of medium boiling range (60-90° C.) petroleum ether, adding them into a closed stainless steel reactor at normal pressure, heating to 50° C., stirring and extracting for 30 minutes, and filtering while hot to obtain petroleum ether insoluble matter;
[0135] Step c, weighing 30 g of the petroleum ether insoluble matter and 120 mL of quinoline into a closed stainless steel reactor at normal pressure, heating to 60° C., stirring and extracting for 60 min, cooling to below 60° C., filtering while hot, and drying to obtain quinoline insoluble matter;
[0136] Step d, transfer 10g of the above-mentioned quinoline insoluble matter to an open tubular furnace, heat it to 360℃ at a rate of 5℃ / min, keep it at a constant temperature for 2h for pre-carbonization, then switch to a closed tubular furnace, introduce argon at a flow rate of 1.5L / min, heat it to 1350℃ at a rate of 5℃ / min, keep it at this temperature for carbonization for 2h, cool it to room temperature, and crush it to obtain a hard carbon material with D50=6μm.
[0137] Application Examples
[0138] The hard carbon materials prepared in Examples 1 to 9 and Comparative Examples 1 to 7 were respectively assembled into sodium ion batteries for electrochemical performance testing, and the specific steps were as follows:
[0139] (1) Preparation of positive electrode sheet: Hard carbon material, conductive carbon black SP, binder SBR and binder CMC were mixed uniformly in a mass ratio of 95.5:1.5:1.5:1.5 to obtain a conductive adhesive. The conductive adhesive was evenly coated on the surface of copper foil with a scraper to form a film with a coating thickness of 100 mm. After drying at 100° C., it was rolled and cut into discs with a diameter of 14 mm, and weighed for later use.
[0140] (2) Assembly of sodium ion battery: A sodium metal sheet with a diameter of 15.8 mm and a thickness of 600 μm was used as the negative electrode, a Celgard 2400 with a diameter of 16 mm and a thickness of 25 μm was used as the separator, the 14 mm positive electrode sheet prepared above was used as the working electrode, and a solution of 1 mol / L NaPF6 dissolved in dimethyl carbonate, ethylene carbonate and ethyl methyl carbonate (volume ratio 3:4:3) was used as the electrolyte to assemble a 2032-type button battery. Five batteries were assembled for each positive electrode material, and a total of five groups of data were tested. After removing the highest and lowest data, the average of the remaining three groups of data was taken as the battery performance data.
[0141] (3) The specific test conditions for the performance of button cells are as follows: at room temperature of 25°C, use a blue electric tester to discharge the assembled button cell at 0.1C (330mAh / g) to 0V, let it stand for 5 minutes, then discharge it at 0.02C to 0V, let it stand for another 5 minutes, and then continue to discharge it at 0.01C to 0V to end the discharge procedure. After standing for 5 minutes, charge it to 2.5V at 0.1C. The ratio of the charge specific capacity to the discharge specific capacity is the first coulomb efficiency at 2.5V. After 2 cycles, change to 1.0CC / 1.0CD (change the current density of 0.02C to a current of 1.0C for constant current charging (CC) and constant current discharging (CD)). After 50 cycles, remove the button cell and record the capacity data, which is the cycle retention rate. The rate test is a constant 1C charge, and the discharge is 0.5C / 1C / 2C / 3C / 4C / 5C / 6C respectively. Each discharge rate is cycled 5 times. The capacity data of 1C and 6C cycles are recorded, and the 6C / 1C capacity rate retention rate is calculated.
[0142] The results are shown in Table 1.
[0143] Table 1
[0144]
[0145] Note: 6C / 1C capacity retention rate % refers to the percentage of 6C corresponding capacity after 5 cycles / 1C corresponding capacity after 5 cycles.
[0146] The extraction yield refers to the weight of the solvent obtained by extraction as a percentage of the mass of ethylene tar; that is, the mass percentage of the tertiary residue to the mass of ethylene tar.
[0147] The carbonization yield refers to the mass ratio of the ethylene tar extraction components before and after carbonization at 1350°C, that is, the weight of the carbonized material / the weight of the third-stage extract residue after drying.
[0148] The results show that the selection of extraction solvent is crucial to the composition of the precursor, which is directly related to the extraction yield and carbonization yield of the solvent, and determines the electrochemical properties of the prepared hard carbon material.
[0149] In summary, the present invention uses lower-cost ethylene tar as raw material, which is different from most methods that use asphalt as raw material. It eliminates the process and cost of preparing asphalt from ethylene tar, and uses the components obtained by three-stage extraction of ethylene tar as hard carbon precursors. Hard carbon materials can be obtained by direct carbonization, which not only eliminates the pre-oxidation step of asphalt or the pre-treatment step of adding a cross-linking agent, but also improves the overall performance of the prepared hard carbon material. The present invention provides a low-cost, high-performance positive electrode material for sodium ion batteries, which is of great significance to the development of sodium ion batteries.
[0150] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a hard carbon material, characterized in that: The steps include: S1, mixing the aromatics-rich oil and the primary extraction solvent uniformly, heating for extraction, and performing solid-liquid separation to obtain a primary extraction liquid; removing the solvent from the primary extraction liquid to obtain a primary extract; S2, mixing the primary extract and the secondary extraction solvent uniformly, heating for extraction, and performing solid-liquid separation to obtain a secondary extract residue; S3, uniformly mixing the secondary raffinate and the tertiary extraction solvent, heating for extraction, cooling, solid-liquid separation, and drying to obtain a tertiary raffinate; S4, pre-carbonizing the tertiary extract at 350°C to 550°C, and then high-temperature carbonizing at 750°C to 1600°C under an inert atmosphere, and crushing to obtain a hard carbon material. Wherein, the polarity of the primary extraction solvent is greater than that of the tertiary extraction solvent and greater than that of the secondary extraction solvent, and the secondary extraction solvent is a non-polar solvent.
2. The method for preparing a hard carbon material according to claim 1, characterized in that: In S1, the aromatics-rich oil includes at least one of ethylene tar, catalytic cracking slurry, medium- and low-temperature coal tar or bio-tar; and / or In S1, the primary extraction solvent includes at least one of quinoline, chloroform, 3-pentanone, 1,1-dichloroethane or cyclohexanone; and / or In S1, the temperature of the heating extraction is 70°C to 90°C, and the time of the heating extraction is 50min to 70min; and / or In S1, the mass volume ratio of the aromatic-rich oil to the primary extraction solvent is 1 g:4 mL to 1 g:6 mL.
3. The method for preparing a hard carbon material according to claim 1, characterized in that: In S2, the secondary extraction solvent is at least one of medium boiling range petroleum ether, n-pentane, n-octane, cyclohexane or cyclopentane; and / or In S2, the mass volume ratio of the primary extract and the secondary extraction solvent is 1g:2mL to 1g:4mL; and / or In S2, the temperature of the heating extraction is 40°C to 60°C, and the time of the heating extraction is 20min to 40min.
4. The method for preparing a hard carbon material according to claim 1, characterized in that: In S3, the tertiary extraction solvent is at least one of n-butanol, isobutanol, amyl alcohol or isopropanol; and / or In S3, the mass volume ratio of the secondary raffinate to the tertiary extraction solvent is 1 g:3 mL to 1 g:5 mL; and / or In S3, the temperature of the heating extraction is 50°C to 70°C, and the time of the heating extraction is 50min to 70min.
5. The method for preparing a hard carbon material according to claim 1, characterized in that: In S4, the temperature is raised to 350°C to 550°C at a rate of 3°C / min to 8°C / min, and the pre-carbonization time is 0.5h to 2h; and / or In S4, the temperature is raised to 750°C to 1600°C at a rate of 3°C / min to 8°C / min, and the high temperature carbonization time is 2h to 10h; and / or In S4, D50 of the hard carbon material is 5 μm to 7 μm.
6. A hard carbon material, characterized in that: The hard carbon material is prepared by the method for preparing the hard carbon material according to any one of claims 1 to 5.
7. A positive electrode, characterized in that Comprising the hard carbon material as claimed in claim 6.
8. Use of the hard carbon material according to claim 6 or the positive electrode according to claim 7 in the preparation of a sodium ion battery.
9. A sodium ion battery, characterized in that: Includes the hard carbon material according to claim 6 or the positive electrode according to claim 7.
10. A battery module, characterized in that: Including the sodium ion battery as described in claim 9.
Citation Information
Patent Citations
Anode material and preparation method thereof
CN102237512A
Mesophase pitch and preparation method thereof
CN104004536A
Method for selectively regulating and controlling graphite-like crystallite sizes and interlayer spaces of heavy aromatic hydrocarbon hard carbon material
CN110921646A
Method for separating, enriching or producing phenolic compounds and method and equipment for processing oil products
CN112569633A
Lithium Ion Capacitor
US20150243449A1